Psycho Heresy The Psychological Seduction of Christianity - Martin; Deidre Bobgan (Santa Barbara EastGate Publishers, 1987)
Psychoheresy: Is about Chistianity and psychology; Examines four commonly-held myths about psychology; Analyzes attempts to integrate psychology with the Bible; Reveals research exposing the fallacies of psychological counseling; Encourages a return to
Keywords: Psychology; Christianity -- Psychology. Psychology and religion. Christentum